Participation and Neutrality of State Civil Apparatus in Direct Regional Election: Surabaya City Case - Santoso, Catur Wibowo Budi (Research and Development Agency Ministry of Home Affairs, 2016)
In relation to the existence of State Civil Apparatus, at least there are two issues that must be observed in the implementation of Regional elections, namely the issues of participation and neutrality of State Civil Apparatus. The phenomenon that occurs during this time is the involvement of the State Civil Apparatus in attendance is still minimum (low). Moreover, it is believed that there are many Civil Apparatus State who is not neutral in the organization of Regional Elections. In this regard, this study aims to analyze the participation and neutrality of State Civil Apparatus. The method utilized in this study is qualitative. The result of the study shows that in general the participation of State Civil Apparatus in Surabaya is adequately good, but the neutrality of State Civil Apparatus has not implemented well enough. There areat least three (3) main factors influencing the participation of Civil State Apparatus, namely the factors of leadership exemplary, commitment to employees, and employee development. As for the neutrality of the State Civil Apparatus, among others, is influenced by the factors of the ambition of employee, primordialism, and working environment of employees.